A 50 year review of basic and applied research in radiant heating and cooling systems for the built environment. (September 2015) - Rhee, Kyu-Nam; Kim, Kwang Woo
Abstract: The radiant heating and cooling (RHC) system has been gaining much popularity due to high thermal comfort, reduced energy consumption, quiet operation, space saving, and so on. For this reason, there have been numerous studies on the RHC system to evaluate the thermal performance of the system and to implement the system for practical applications. This study conducted a literature review on the basic and applied research in RHC systems for the built environment. The objective of this review is to find out the research trend of the RHC system, to discover main issues for the RHC system understanding, and to suggest further studies for the system development. In this study, a comprehensive review was conducted, in terms of thermal comfort, thermal analysis including heat transfer model, heating/cooling capacity, CFD analysis, energy simulation, system configuration and control strategies. The results showed that the RHC system has been continuously developed, modified and improved to achieve better thermal comfort and energy efficiency. Based on the review results, several topics for future studies were suggested, which are required to overcome the limitations of the RHC system for extending its application to various building types, climate, and so on. Highlights: A comprehensive review was conducted for the radiant heating and cooling system. Research topics were analyzed for the publications in Building and Environment. The review dealt with researches on comfort, heat transfer, CFD, and control. Based on the review, several topics are suggested for the future study.